Mosul Operation: The Endgame for IS? - Abdul Basit (2016)
The loss of Mosul will be a huge setback for the self-proclaimed Islamic State group, posing it an existential threat. However, confusing the loss of territory with the defeat of IS will be premature and over-simplistic.